2005
DOI: 10.1159/000091131
|View full text |Cite
|
Sign up to set email alerts
|

Social Disruption Stress Exacerbates α-Galactosylceramide-Induced Hepatitis in Mice

Abstract: Objective: Psychosocial stress has been suggested as a possible aggravating factor in liver diseases, however, the underlying mechanism has yet to be clarified. Recently, our research revealed that electric foot-shock stress aggravated NK1.1 Ag+ T cell-dependent α-galactosylceramide (α-GalCer)-induced hepatitis in mice via a mechanism mediated by endogenous glucocorticoids. In this study, we examined whether or not such aggravation could be applied to a psychosocially stressful situation, e.g. socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Here we describe a unique murine model in which social stress and allergen exposure provides a platform to investigate the psycho-endocrine-immunological axis that regulates airway inflammation. Social disruption, a well characterized psychological stressor, has been used by our laboratory and others to assess the impact of a semi-natural stressor on immune function (35, 3942). In this model a previously established social hierarchy of a stable cohort of younger male mice is disrupted by a large, aggressive male that confronts and repeatedly defeats the cage residents.…”
Section: Discussionmentioning
confidence: 99%
“…Here we describe a unique murine model in which social stress and allergen exposure provides a platform to investigate the psycho-endocrine-immunological axis that regulates airway inflammation. Social disruption, a well characterized psychological stressor, has been used by our laboratory and others to assess the impact of a semi-natural stressor on immune function (35, 3942). In this model a previously established social hierarchy of a stable cohort of younger male mice is disrupted by a large, aggressive male that confronts and repeatedly defeats the cage residents.…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments, a number of types of stress have been created and used in several disease models. In general, each stress is characterized according to a distributed ratio of physical and psychological burdens: for example, a physical burden is far more dominant in forced swimming, immobilization, and electrical FS stress (22,(29)(30)(31), whereas a psychological burden is created by social isolation stress, water avoidance stress, and social disruption stress (24,32,33). The communication box method, designed by Ogawa and Kuwahara (34), has Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that repeated social stress in mice is associated with decreased GC sensitivity of immune cells and excessive inflammation Engler et al, 2005;Johnson et al, 2004;Merlot et al, 2004;Sonoda et al, 2005;Stark et al, 2001). For example, lipopolysaccharide (LPS)-stimulated splenocytes from mice that repeatedly experienced acute encounters with an aggressive conspecific exhibited considerably higher cell survival in the presence of corticosterone (CORT) and showed greatly enhanced production of pro-inflammatory cytokines compared to splenocyte cultures from non-stressed controls (Avitsur et al, 2005Merlot et al, 2004;Stark et al, 2001).…”
Section: Introductionmentioning
confidence: 99%